Hispanic Socio-Religious Minorities in Secondary School Textbooks in Spain (1970–2018) - Moreno-Díaz del Campo, Francisco Javier (2021)
Introduction. Western societies face the challenge of introducing and developing educational methodologies in order to ease the integration of minorities and promote the attention to the diversity of an increasingly and heterogeneous group of students. History can contribute to this mission by analyzing the past of groups that were persecuted because of their origin, ideas, or beliefs. Methods. This paper examines the narratives and methodologies implemented in the last half-century in the several Spanish secondary education levels to inspect the history of Jew converts and Moriscos, the two main Spanish socio-religious minorities during the Early Modern Period. Conducting the study required analyzing more than thirty school textbooks; these texts were published between 1973 and 2018. They have been used in the legislative context defined by the four applicable education programs from 1970 to the present in the two secondary education levels in Spain (compulsory education and high school). The analysis of these contents was conducted considering their place in the general programming of each educational law, the space occupied by the explanation in each didactic unit, and the interpretation given to the role that both minorities played in Spain during the Early Modern Period. This paper aims to define the argumentative line used to introduce the evolution of both social groups in the teaching of Hispanic history in the 16th and 17th centuries. Results. Thanks to examining contents, exercises, and complementary materials, we can verify that the study of both minorities is one of the most important issues in Spanish history in the Early Modern Period. However, it has been observed that, in the last fifty years, there are no significant modifications in textbooks used in secondary education. Both groups are examined prioritizing political and institutional considerations, where the social and cultural issues are relegated to the background. Discussion. The persistence of these discursive inertias cannot be just explained from the importance of nationalist narratives in the way our history is narrated, but also on the basis of the obvious lack of connection between taught/learned and researched history.